Expanding tam and investigating the factors that effects on consumers' intention to adopt mobile banking - Haitham Jouda (Financial Internet Quarterly, 2020)
Purpose The main objective of this study is to expand the technology acceptance model (TAM) by examining the factors affecting the adoption of mobile banking services by the customers of Palestinian banks and to design a comprehensive model based on TAM and TPB and additional constructs. Design/methodology/approach This study used the quantitative approach with cross sectional research design and a questionnaire as a data tool. From the six big cities in Palestine, we surveyed 1000 banking consumers. The samples include different characteristics. For construct relationship analysis this study applied partial least squares (PLS). Findings The study framework provides a complete view of mobile banking services. This framework takes into consideration more determinants for prediction than other studies on the adoption of innovations. The results of using this model managed to clarify nearly 77.4 percent of the dependent variable (intention to adopt mobile banking service) variation. This is a much greater value than those of the previous studies.
Keywords: B30; B31; B32; 330; banking e-services; TPB; TAM; technology adoption; attitude; institutions; Palestine